2001
DOI: 10.1096/fj.01-0518fje
|View full text |Cite
|
Sign up to set email alerts
|

Influence of α‐melanocyte‐stimulating hormone and of ultraviolet radiation on the transfer of melanosomes to keratinocytes

Abstract: The epidermal melanin unit in human skin is composed of melanocytes and keratinocytes. Melanocytes, located in the basal layer of the epidermis, manufacture melanin-loaded organelles called melanosomes. Through their dendritic processes, melanocytes distribute melanosomes to neighboring keratinocytes, where their presence confers to the skin its characteristic color and photoprotective properties. In this study, we used murine melanocytes and keratinocytes alone and in coculture to characterize the processes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
129
3
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(140 citation statements)
references
References 54 publications
7
129
3
1
Order By: Relevance
“…␣-MSH and UV radiation are well known as major physiological signals that modulate skin pigmentation [1,22]. Melanocytes react to these signals by proliferation, increased dendriticity and elevated pigment synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…␣-MSH and UV radiation are well known as major physiological signals that modulate skin pigmentation [1,22]. Melanocytes react to these signals by proliferation, increased dendriticity and elevated pigment synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…Physiological factors such as pro-opiomelanocortin-derived peptides (e.g. a-MSH) (Virador et al, 2002) have been implicated. Here we for the first time showed that melanin transfer and filopodia formation can be markedly stimulated by BMP6 incubation in fully-matched MC-KC co-cultures.…”
Section: Discussionmentioning
confidence: 99%
“…However, just how melanin is transferred to neighbouring KCs has remained stubbornly enigmatic (Van Den Bossche et al, 2006). Several hypotheses have been proposed including: (i) cytophagocytosis of MC dendrite tips (Seiberg et al, 2000), (ii) exocytosis of melanosomes and subsequent uptake via phagocytosis into KC (Marks and Seabra, 2001;Virador et al, 2002) and (iii) filopodia-mediated melanosome transfer (Singh et al, 2010;Singh et al, 2008;Beaumont et al, 2011;Zhang et al, 2004;Scott et al, 2002). The role of filopodia in the transfer of melanosomes to keratinocytes was originally proposed by Scott and colleagues (Scott et al, 2002), and we extended this further in our recent report that proposed a 'filopodial-phagocytosis model' for melanin transfer (Singh et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…10) Skin pigment disorders such as melasma and postinflammatory hyperpigmentation are characterized by increased melanosome production and accumulation. 11) Hyperpigmentation has psychosocial and cosmetic relevance; therefore, considerable effort has been devoted to screening effective depigmenting agents. The ideal depigmenting agent exerts rapid, potent, and selective bleaching effects on melanocytes, has no side-effects, and permanently removes undesired pigment.…”
Section: -7)mentioning
confidence: 99%